Current Applications and Future Perspectives of Mxenes: 2D Materials - Laura Gobbi; Marco Ruggeri; Margherita Tiradritti; Giuliana Vinci (Current Approaches in Science and Technology Research Vol. 7, 2021)
The isolation of graphene in 2004 sparked interest in the study of 2-dimensional (2D) materials. MXenes are a new family of metal carbides of transition 2D, nitrides, and carbonitrides. Since their discovery in 2011, they have attracted the scientific and industrial community’s interest thanks to their unique properties, including high electrical conductivity, hydrophilic nature, excellent thermal stability, and ample spacing between layers and high surface areas. We briefly examine MXenes’ primary synthesis processes, characteristics, and some of the most interesting possible uses currently known, such as environmental remediation, energy storage, biomedical applications, and food packaging, in this paper.